DETERMINAN TINGKAT PRESENTEEISM DI INSTANSI X PADA TAHUN 2023 - Karomah Devi Astriningrum (2024)
Presenteeism is the behavior of workers who are present to do their work when they experience health problems. Presenteeism behavior is quite worrying because it can harm the company and also worsen health. This research aims to determine the most dominant factors in the level of presenteeism at Institution X in 2023. The research used a cross-sectional study design and data was obtained directly by filling out a questionnaire (primary data). The research was conducted in November - December 2023 using a sample of 205 PPNPN employees at a Non-Ministerial Government Institution in Central Jakarta. Data analysis used the Chi-Square and Multiple Logistic Regression tests to achieve research objectives. After being controlled for job satisfaction, the analysis results show that workaholic (P < 0,001; POR = 3,703; 95% CI = 1,8 - 7,6) is the factor that dominates the level of presenteeism. The existence of presenteeism behavior can be a concern for institutions to create a good work environment so that the prevalence of presenteeism can decrease and employees maintain productivity without harming their health.